2021
DOI: 10.3390/su13095290
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Corporate Ethical Management on Trade Relationship Trust and Commitment: B2B

Abstract: This study investigated whether three components of ethical management—awareness, operation, and practice—have a positive effect on corporate trust and relationship commitment in business-to-business (B2B) transactions. The study examined whether the trust formed in transactions, or relationship commitment, affects the establishment of long-term oriented relationships between companies. Further, it also aimed to determine the extent to which the authenticity of ethical management serves as a moderator that all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
1
0
1
Order By: Relevance
“…Promotion as supplier's competitive factors support will positively affect retailers' product recommendations. Fei et al (2021) suggested that the formation of a positive relationship between suppliers and distributors is effective in improving sales and sales power. Van Der Grijp et al (2005) mentioned that in the pesticide industry, retailers consider the formation of relationships with suppliers important, and that product sales and recommendations to trusted suppliers are generally made.…”
Section: Research Model and Hypothesis Developmentmentioning
confidence: 99%
“…Promotion as supplier's competitive factors support will positively affect retailers' product recommendations. Fei et al (2021) suggested that the formation of a positive relationship between suppliers and distributors is effective in improving sales and sales power. Van Der Grijp et al (2005) mentioned that in the pesticide industry, retailers consider the formation of relationships with suppliers important, and that product sales and recommendations to trusted suppliers are generally made.…”
Section: Research Model and Hypothesis Developmentmentioning
confidence: 99%
“…Dentro del marketing, las relaciones de transacción business to business (b2b) se centran en aquellas operaciones que se llevan a cabo entre empresas, sin tener en cuenta al cliente final, y que hacen referencia a cualquier actividad de la empresa dentro de su cadena de valor (Fei et al, 2021;Hague & Hague, 2018). En esta modalidad, las empresas participantes, especialmente en el sector industrial, necesitan la presencia de la figura del vendedor personal, interconectando empresa vendedora y compradora, a través de una oferta personalizada que cumpla con las expectativas concretadas previamente por el cliente.…”
Section: Marco Teóricounclassified